2021
DOI: 10.3390/su132212919
|View full text |Cite
|
Sign up to set email alerts
|

Energy Evolution: Forecasting the Development of Non-Conventional Renewable Energy Sources and Their Impact on the Conventional Electricity System

Abstract: The development of the world’s electric power systems goes back over a century. During this period, the overwhelming majority of states have formed stable, typically centralized systems for generation, transmission, and distribution of electrical energy. At the same time, technologies, primarily for energy generation, are steadily developing, which leads to the emergence of potentially effective technological solutions based on fundamentally new energy sources. The most rapidly expanding group at the moment ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…3 [15]. In order to keep the global temperature below this limit, it is observed that in the 2030s the percentage of RES energy should reach approximately 56%, 88% in 2040 and 100% by 2050 [15], [16], [17]. Fig.…”
Section: Forecasting the Evolution Of Res Integration To Stop Climate...mentioning
confidence: 99%
“…3 [15]. In order to keep the global temperature below this limit, it is observed that in the 2030s the percentage of RES energy should reach approximately 56%, 88% in 2040 and 100% by 2050 [15], [16], [17]. Fig.…”
Section: Forecasting the Evolution Of Res Integration To Stop Climate...mentioning
confidence: 99%